Effect of Therapeutic Communication on Anxiety Levels in Preoperative Patients - Gustini Gustini; Isymiarni Syarif; Zusana A Sasarari; Ummul Khair; Anggeraeni Anggeraeni (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Therapeutic communication towards decreasing anxiety levels in preoperative patients. Through a deeper understanding of the role of therapeutic communication in caring for preoperative patients, we can improve the quality of health care and patient well-being. The purpose of the study was to determine the effect of therapeutic communication on anxiety levels in preoperative patients. This research design uses quasi-experiments with the Non-Equivalent Control Group research design which in this design consists of a control group and an experimental groupThe Wilcoxon test shows that the p-value obtained is 0.001, and the Z value is -3.256. A P-value of 0.317, Mann Whitney U-Test statistical test with computerized assistance and obtained a Z value of -3.867 with Asymp Sig of 0.000It can be concluded that the provision of therapeutic communication has an effect on reducing anxiety levels in preoperative patients. Providing therapeutic communication in preoperative patients with an empathetic, informative, and supportive communication approach can have a positive effect on reducing anxiety levels in patients. By listening, providing clear information, providing emotional support, providing questioning opportunities, and teaching relaxation techniques, medical personnel can help patients feel calmer, overcome uncertainty, and feel better prepared for surgical procedures. This can contribute to patient comfort and minimize the negative impact of anxiety on the surgical process and postoperative recovery